Teknologi Open Source Radio Streaming Berbasis Website dan Android - Febrian Wahyu Christanto; Bernadus Very Christioko; Vensy Vydia (Universitas PGRI Semarang, 2020)
Music is something that can not be separated from human life. This is what makes technology develop so rapidly that radio emerges. Radio is a very important media in delivering information to the public. Along with the development of the emergence of internet technology that allows information to be accessed by all citizens wherever located. So that radio is now transforming with the internet so that the delivery of information is not limited by geographical areas as is the case with conventional radios that rely on transmitters so that when listeners travel outside the city, favorite radio is impossible to hear. UKM Radio Ekspresi Mahasiswa Universitas Semarang (REMUS) is a radio community that currently does not have facilities such as transmitters and mixers so that the UKM activities are only focused on Lab activities. Radio that is offline and visits to cause the membership of these UKM ups and downs. Website and Android-based open-source radio streaming technology is a solution for this UKM because besides being affordable, UKM REMUS can broadcast online so that it can be listened to by students and the public at large. This research uses the Prototype system development method and system implementation using a combination of open source applications namely are Wordpress, Icecast2, dan Android Studio in the server-side then use Winamp, SAM Broadcaster, dan Shoutcast DSP the radio announcer side. The results of the 20 respondents members of UKM, as many as 85% agreed to this radio streaming system. It is expected that the results of this study are the sustainability and the percentage of the membership of UKM REMUS will run well.